38 Diverting the rising tide: the impact of a modern heart failure community outreach programme. (October 2018) - O'Connor, C; Caples, N; Cronin, E; Kumar, J; Chui, H; Herlihy, C; Hennessy, A; O'Dea, J; O'Callaghan, P; Owens, P
Abstract : Background: There are 90 000 patients in Ireland suffering from heart failure, with a further 10 000 being diagnosed every year. This places significant burden on hospital resources nationally, resulting in the use of 2 31 042 bed days at a total cost of €277 million. Various models of heart failure service have been suggested; primary care centred, community centred and hospital centred. Our unique community outreach model (south Eastern Community Heart failure Outreach clinic (ECHO clinic)) strength lies in the maintaining of close links with specialised staff in a hospital setting whilst providing accessible care for patients with severely reduced functional status. Aims: To study the impact of a community heart failure outreach programme in admission/readmission rates and improvement in left ventricular ejection clinic (LVEF). Methods: Both retrospective and prospective cohort analyses was performed on patients attending the south Eastern Community Heart failure Outreach 'ECHO' clinic over a period of one year. Each patient was given likert patient satisfaction questionnaires. Additional patient level data was sourced from electronic and written records. Standard Bayesian statistics were employed to conduct the analysis. Results: A total of 74 patients were recruited from the ECHO clinic. Of these, complete datasets for 34 patients were available for analysis. Before enrolment, patients had an average of 1.3 admissions and after enrolment had an average of 0.5 admissions. Unequal variance was proven by Anderson-Darling and so Wilcoxon rank sum test was performed with a p value of 0.001533. There was also an associated reduction in bed days following recruitment into the ECHO clinic (407 vs 105) which was significant with use of Wilcoxon rank sum test (p=0.000302). On an individual patient level, this equates to a reduction in average length of stay per heart failure admission from 9.25 to 5.5 days, which was significant by signed rank test (p-value 0.05). Specialised outreach heart failure management was also associated with an increase in LVEF (26.6% vs 36.8%, p-value 0.00672). Regarding patient's experience of attending the ECHO clinic, 88% of respondents strongly agreed that it was easily at access and 89% of respondents strongly agreed that it was preferable to attend the local outreach programme rather than the local hospital (see figure 1). Conclusion: Implementation of a novel 'community outreach' heart failure programme significantly reduces hospitalisation and inpatient bed days but also reduced length of stay per admission after enrolment. Enrolment was associated with an improvement in LVEF. Patient satisfaction ranked highly with the community outreach model of heart failure management.